Exploring English Teachers' Attitudes Toward Technology-Supported Reflection in Professional Development - Nufus, Tatu Zakiyatun; Mahmud, Ade (Journal of English Education and Teaching, 2024)
This study explores English teachers' attitudes toward technology-supported reflection in professional development, focusing on its role in fostering deeper engagement with the new teaching methods. The research addresses the issue of limited sustained reflection in professional development programs, which often undermines long-term teacher growth. The study aims to understand how integrating tools such as Padlet and Google Doc into reflective practices influences teachers' attitudes and enhances their professional development experiences. Using a qualitative case study design, ten English teachers were purposively selected based on their successful completion of assigned tasks during a one-month online professional development program centered on new teaching methods. Data were collected through semi-structured interviews, reflective journals, and observations of the teachers’ interactions with the technology tools provided for reflection. Findings revealed that most participants held positive attitudes toward technology-supported reflection, citing its convenience, ability to provide immediate feedback, and facilitation of collaborative discussions. However, some expressed challenges, including technical issues and initial resistance to adapting to digital tools. The study highlights the potential of technology to make reflective practices more engaging and practical for teachers. Implications suggest that professional development programs should integrate user-friendly technology to foster reflective practices, ultimately enhancing teaching efficacy and teacher satisfaction.